Stewardship as an Innovation and Creativity Tool in the Online Environment of Polish Public Benefit Organizations - Marian OLINSKI; Piotr SZAMROWSKI (Communications of International Proceedings, 2021)
This paper explores the degree of innovativeness measured by the level of application of the stewardship concept in Polish public benefit organizations, as well as the dependence between specific features of these organizations and the intensity of the stewardship concept application. The results have revealed a statistical relationship between the size of a PBO and the implementation of the stewardship concept. The research suggests that the type of PBO activity does not affect the implementation of the stewardship concept.
Keywords: Stewardship; Non-Profit Organizations; Innovation; Relationship